Kuat Tekan Batako Ringan dengan Material Latrit dan Foam Agent - Rahmat Rahmat; Martheana Kencanawati; Suheria Mulia Devi (JST (Jurnal Sains Terapan), 2018)
This research intends to improve laterite material as an alternative filler composite mortar bricks, began with analyzing substitution of mortar sand composite, to its concrete mortar composite according to characteristic and compressive strength,  as comparison for common bricks  building materials had done. This research was pointed, to maximize the bricks compressive strength with laterite addition by experiment method. Samples were made with two variations, which is normally and laterite bricks (as sand substitution is 50%) and the compressive strength gain normal mixture was at 25,09 kg/cm2. Meanwhile, by using 50% bricks substitution and 50% sand substitution, the results was 28,56 kg/cm2. It can be assumed that compressive strength material can increase the compressive strength.